Research on soil spatial heterogeneity and pattern of Huangniling red soil watershed - LU Jian-Bo; YANG Jing-Ping (浙江大学学报. 农业与生命科学版, 2002)
Huangniling red soil watershed in Anji county of Zhejiang province is selected as a case study, soil properties of different samples are analysed by use of grid cell method, soil spatial heterogeneity and pattern are studied with the supporting of geostatistics and geographic information system (GIS). The results show that: soil spatial heterogeneity of this watershed is evident; orders of Cv (Coefficient of Variation) are: quick-acting K>quick-acting P>total N and content of organic matter >pH; the spatial tendency of total N and content of organic matter is similar and they have closely linear relationship; the spatial pattern of quick-acting P and quick-acting K is also similar; soil spatial pattern is deeply affected by human activities.